Aplicação do mapeamento vetorial para biomoléculas - Sacco, Antonio Cesar Silva (Universidade Federal de São Carlos, 2017)
The main focus of this work was to study two types of non-covalent interactions: π interactions and hydrogen bonds. This type of study is necessary when one wants to analyze, for example, enzyme-ligand or DNA-ligand complexes. With the help of graphic visualization programs the researcher ends up analyzing, in general, only part of the studied biological molecule. A more complete study becomes more difficult given the amount of atoms and interactions in biological molecules. Thus, an algorithm was developed to evaluate all non-covalent π interactions and hydrogen bonds present, being intra or intermolecular, thus obtaining all the distances, angles and atoms involved, using predefined parameters or parameters defined by the researcher. The interactions so obtained can be viewed with an external graphic program. Thus, the computational tool called WIM (Weak Interaction Mapping) was developed, transforming the vector mapping into a research tool. The automation of the process using WIM software to investigate the non-covalent interactions made possible to study a series of DNA structures with and without ligands, and to verify the existence of certain patterns generated by this type of interactions, as well as to study in detail the introduced deformations by the ligands in different DNA structures. The WIM software received a favorable opinion in the process of protection of the program, Process AIn PC 2017/004 -UFSCar, on 06/27/2017.
Vector mapping applied to biomolecules
Mapeo vectorial aplicado a biomoléculas
Keywords: Mapeamento vetorial; Interações π; Interações eletrostáticas; Ligações de hidrogênio; Vector mapping; π interaction; Electrostatic interactions; Exploration and analysis of π interactions; ENGENHARIAS::ENGENHARIA BIOMEDICA::BIOENGENHARIA::MODELAGEM DE FENOMENOS BIOLOGICOS; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO; CIENCIAS BIOLOGICAS::BIOQUIMICA; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS::PROTEINAS